2010
DOI: 10.1603/en09236
|View full text |Cite
|
Sign up to set email alerts
|

Biological Parameters ofScirtothrips dorsalis(Thysanoptera: Thripidae) on Selected Hosts

Abstract: Since its establishment in Florida in 2005, Scirtothrips dorsalis Hood, a highly polyphagous species, has become an economically important pest of ornamental plants and a potentially significant pest of vegetable and fruit crops. Fruit and vegetable production in Florida is trending toward significant adoption of organic methods and use of widely dispersed small fields in rapidly urbanizing landscapes. Landscape plants may serve as refugia from which S. dorsalis recruits can disperse to nearby fruit and vegeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 16 publications
1
38
2
1
Order By: Relevance
“…Chen, Lin, Chiu, & Shih (2013) and Kang, Lee, & Kim (2015) found that the development of S. dorsalis on mango decreased from 21.5, 14.8, 12.1, to 9.8 days at 20, 24, 28, and 32 °C , respectively. Seal, Klassen, & Kumar (2010) found that host as factor determined the developmental duration of S. dorsalis reared on bean, eggplant, pepper, rose, squash and tomato in a constant temperature of 26 °C had a mean duration of 20.3 ± 0.3; 19,9 ± 0,6; 17.8 ± 0.3; 18.8 ± 0.4; 20.2 ± 0.5 and 20.6 ± 0.3 days, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen, Lin, Chiu, & Shih (2013) and Kang, Lee, & Kim (2015) found that the development of S. dorsalis on mango decreased from 21.5, 14.8, 12.1, to 9.8 days at 20, 24, 28, and 32 °C , respectively. Seal, Klassen, & Kumar (2010) found that host as factor determined the developmental duration of S. dorsalis reared on bean, eggplant, pepper, rose, squash and tomato in a constant temperature of 26 °C had a mean duration of 20.3 ± 0.3; 19,9 ± 0,6; 17.8 ± 0.3; 18.8 ± 0.4; 20.2 ± 0.5 and 20.6 ± 0.3 days, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The laid down mango leaf inside the Petri dish was infested with ten female adult of S. dorsalis for 24 hours for oviposition. The upper part of the leaves was observed every four hours for the emergence of first larval instar (Seal, Klassen, & Kumar, 2010). The twenty newly hatches larval instars were transferred to new leaves.…”
Section: Methodsmentioning
confidence: 99%
“…The genetic differences between these samples was considered to be too great to support the conclusion that separate host races were present. According to Seal et al (2010), different populations of this pest have host preferences without substantial modifications to life history traits such as development, survival and fecundity. Toda et al (2014) found a new strain of S. dorsalis infesting capsicum in addition to mango and tea in Japan.…”
Section: Intraspecific Diversitymentioning
confidence: 99%
“…Given the high polyphagy of S. dorsalis, many wild plant species can serve as a reservoir for dispersal to cultivated plants (Seal et al, 2010). The availability of the host plants significantly increases the success of dispersal.…”
Section: Spread Capacitymentioning
confidence: 99%
See 1 more Smart Citation